2004
DOI: 10.2134/jeq2004.1010
|View full text |Cite
|
Sign up to set email alerts
|

Cover Cropping to Reduce Nitrate Loss through Subsurface Drainage in the Northern U.S. Corn Belt

Abstract: Despite the use of best management practices for nitrogen (N) application rate and timing, significant losses of nitrate nitrogen (NO3(-)-N) in drainage discharge continue to occur from row crop cropping systems. Our objective was to determine whether a autumn-seeded winter rye (Secale cereale L.) cover crop following corn (Zea mays L.) would reduce NO3(-)-N losses through subsurface tile drainage in a corn-soybean [Glycine mar (L.) Merr.] cropping system in the northern Corn Belt (USA) in a moderately well-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
229
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(252 citation statements)
references
References 21 publications
18
229
5
Order By: Relevance
“…Zhu et al (2005) reported nitrate leaching was the main route of N loss and accounted for the nearly one-third reduction in N (600 kg N ha À1 ) application rate that was possible instead of the conventional practice (1800 kg N ha À1 ) in hot pepper greenhouse cropping system in Shouguang, Shandong province. Thus, despite the use of best management practices for N application rate and timing, significant losses of nitratenitrogen in drainage discharge continue to occur from cropping systems (Strock et al, 2004). In our experiment at least 386 kg N ha À1 (not including N mineralization) per season was lost from the plant-soil system.…”
Section: Discussionmentioning
confidence: 72%
“…Zhu et al (2005) reported nitrate leaching was the main route of N loss and accounted for the nearly one-third reduction in N (600 kg N ha À1 ) application rate that was possible instead of the conventional practice (1800 kg N ha À1 ) in hot pepper greenhouse cropping system in Shouguang, Shandong province. Thus, despite the use of best management practices for N application rate and timing, significant losses of nitratenitrogen in drainage discharge continue to occur from cropping systems (Strock et al, 2004). In our experiment at least 386 kg N ha À1 (not including N mineralization) per season was lost from the plant-soil system.…”
Section: Discussionmentioning
confidence: 72%
“…Cover crops have long been used to protect the soil from erosion; however, few studies have investigated the impact of cover crops on tile nitrate losses. Although Qi et al (2011) did not detect a reduction in tile nitrate yield with a rye cover crop, Strock et al (2004) found a modest reduction in tile nitrate yield of 13%, whereas Kaspar et al (2007) found large tile nitrate reductions (59%) using rye as a winter cover crop. Cover crops may be the only practice that can reduce both erosion and tile nitrate yields.…”
Section: Cover Cropmentioning
confidence: 82%
“…N leaching outside the growing season may appear to be completely outside the control of the grower because of high residual N min and high precipitation typical of the summer fallow season on the North China Plain. To prevent leaching of nitrogen after harvest and potential contamination of groundwater, the nitrogen used for the N min buffer can be removed from the soil by growing a cover crop of another species (Strock et al 2004;Weinert et al 2002). Ju et al (2007) demonstrated the high risk of nitrate leaching in the summer season and suggested that deep-rooted species such as corn can be used as a catch crop to intercept soil nitrate deep in the soil profile to control nitrate leaching.…”
Section: Discussionmentioning
confidence: 99%
“…Using these strategies 73% of N fertilizer was saved in a continuous three-season greenhouse tomato cropping system (He et al 2007). However, significant losses of nitrate-N in drainage discharge still continued to occur because of long-term surplus nutrient supply and very high soil fertility through excessive application of organic manures and nitrogen fertilizers, together with excessive irrigation (He et al 2007;Strock et al 2004) and heavy rainfall events in the summer season when the polyethylene covered greenhouses are opened on the North China Plain (Chen et al 2005;He et al 2003).…”
Section: Introductionmentioning
confidence: 99%